Establishing Climate-Smart Villages in the ASEAN Region to Improve Food Security and Resiliency in Local Communities - SEARCA (2019)
The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA), in partnership with the International Institute of Rural Reconstruction (IIRR) and the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS), organized a workshop titled Establishing Climate-Smart Villages (CSVs) in the ASEAN Region to Improve Food Security and Resiliency in Local Communities on 9-13 July 2019 to demonstrate the principles and processes behind the application of climate-smart agriculture in communities vulnerable to the worsening impacts of climate change. The workshop consisted of two components, namely: lectures and re-entry action planning activities, which were held at SEARCA Headquarters in Los Baños, Laguna, and a roving workshop that showcased the different CSVs established in the municipality of Guinayangan in Quezon Province, Philippines.